'I've never drunk very much water and I still don't, and I see no reason to do so': a qualitative study of the views of community-dwelling older people and carers on hydration in later life. (10th December 2019) - Bhanu, Cini; Avgerinou, Christina; Kharicha, Kalpa; Bauernfreund, Yehudit; Croker, Helen; Liljas, Ann; Rea, Jennifer; Kirby-Barr, Maggie; Hopkins, Jane; Walters, Kate
Abstract: Background: dehydration is associated with significant adverse outcomes in older people despite being largely preventable and treatable. Little research has focused on the views of community-dwelling older people on hydration, healthy drinking and the perceived importance of drinking well in later life. Objectives: to understand community-dwelling older people and informal carers' views on hydration in later life and how older people can be supported to drink well. Methods: qualitative study using interviews and a focus group exploring hydration and nutrition in later life (24 older people at risk of malnutrition and dehydration, 9 informal carers) and thematic analysis. Results: this article presents the findings on hydration alone. Four themes are presented: perceptions of healthy drinking, barriers to and facilitators of drinking in later life and supporting older people to drink well. The perceived importance of adequate hydration in later life was polarised. Concerns about urinary incontinence and knowledge gaps were significant barriers. Consideration of individual taste preference and functional capacity acted as facilitators. Distinct habitual drinking patterns with medications and meals exist within individuals. Many relied on thirst at other times or when fluid demands are greater (such as hot weather), a known unreliable prompt in later life. Conclusions: older people could be supported to drink well by building upon existing habitual drinking patterns. Primary care and public health should consider individual barriers, facilitators and tailored education. A multidisciplinary approach to promote hydration should be incorporated into care for older people with more complex needs.